Successful treatment of pyoderma gangrenosum with guselkumab - Sofia Botvid; Claus Zachariae; Lone Skov; Jakob Ferløv Schwensen (JEADV Clinical Practice)
Abstract Guselkumab, a monoclonal antibody known for its effective inhibition of T‐cell‐immunoactivity through specific binding to interleukin‐23 (IL‐23)‐cytokines, may be used for off‐label treatment of pyoderma gangrenosum (PG). Herein, we report two successful cases of off‐label treatment for PG, using guselkumab, after unsuccessful treatments with standard regimens of corticosteroids, immunomodulating therapy and other biological agents. Case 1 involves a 39‐year‐old female with treatment‐resistant peristomal PG post‐colectomy and ileostomy. Case 2 features a 35‐year‐oldfemale with treatment‐resistant PG, presenting with deep necrotic lower extremity ulcers. In both cases, we observed remarkable healing within months to a year. These two cases support the potential use of systemic IL‐23‐targetedtherapy for treatment‐resistant PG.